(untitled) (Research, Society and Development, 2022)
This research aimed to map the productions developed on teaching in higher education from 2012 to 2020 in the Theses and Dissertations Database - BDTD, searching for the following descriptors: training; teaching work and higher education. Thus, answers to the problem were sought: What are the most recurrent approaches evidenced in relation to teaching in higher education? The methodology was outlined by a bibliographic study and the results indicate that teaching in higher education is a theme that opens up a range of possibilities for topics such as teaching knowledge, pedagogical practices, pedagogical training, continuing education, among others, to be brought to the field of research and, thus, can contribute to the exercise of the profession at this level of education, which still needs further studies.